Analysis the effects of techno-economic parameters on the economy of underground mining in Jama Bor - Milić Vitomir; Svrkota Igor; Petrović Dejan (Mining and Metallurgy Engineering Bor, 2015)
When a new mining method is designed, it is necessary to define the optimal parameters of method. Applicability of a method in certain conditions is tested through determination of each relevant method parameter. Their values have to be acceptable. This paper presents a case study for analyses of parameters related to the ore body Borska Reka. The analysis was focused on determination the share of costs in the final price, ore value and copper production economy.